"A woman's life is tension": A gendered analysis of women's distress in poor urban India. (June 2021) - Atal, Saloni; Foster, Juliet
The mental health of women living in poverty is a growing public health concern, particularly in India where the burden of illness is compounded by critical shortages in mental health providers and fragmented services. This was an exploratory study which sought to examine low-income women's perceptions of mental illness and its management in the context of urban poverty in India. This research was prompted by the lack of empirical studies documenting how women in marginalized sections of society understand mental illness. Data were collected through a combination of 10 focus group discussions and two individual interviews with a total of 63 women residing in low-income areas of Mumbai. Social representations theory was used to explore shared meanings of mental illness among women in this setting. Thematic analysis of the data showed that women use the expression "tension" to talk about mental illness. Tension was described both as an ordinary part of life and a condition having its origins in more profound gender-related stressors, particularly pressures surrounding motherhood, chronic poverty and domestic conflict. Approaches to managing tension were pluralistic and focused on the resumption of social roles. Findings are consistent with other studies in similar cultural contexts, suggesting a shared, transnational character to women's distress and the need for scholarship on women's mental health in low-income settings to be more attuned to gendered forms of marginalization.